Dual Roles for Yeast Sti1/Hop in Regulating the Hsp90 Chaperone Cycle - Reidy, Michael (Genetics, 2018)
The Hsp90 chaperone is regulated by many cochaperones that tune its activities, but how they act to coordinate various steps in the reaction cycle is unclear. The primary role of Saccharomyces cerevisiae Hsp70/Hsp90 cochaperone Sti1 (Hop in mammals) is to bridge Hsp70 and Hsp90 to facilitate client transfer. Sti1 is not essential, so Hsp90 can interact with Hsp70 in vivo without Sti1. Nevertheless, many Hsp90 mutations make Sti1 necessary. We noted that Sti1-dependent mutations cluster in regions proximal to N-terminal domains (SdN) or C-terminal domains (SdC), which are known to be important for interaction with Hsp70 or clients, respectively. To uncover mechanistic details of Sti1–Hsp90 cooperation, we identified intramolecular suppressors of the Hsp90 mutants and assessed their physical, functional, and genetic interactions with Hsp70, Sti1, and other cochaperones. Our findings suggest Hsp90 SdN and SdC mutants depend on the same interaction with Sti1, but for different reasons. Sti1 promoted an essential Hsp70 interaction in the SdN region and supported SdC-region function by establishing an Hsp90 conformation crucial for capturing clients and progressing through the reaction cycle. We find the Hsp70 interaction and relationship with Sti1/Hop is conserved in the human Hsp90 system. Our work consolidates and clarifies much structural, biochemical, and computational data to define in vivo roles of Sti1/Hop in coordinating Hsp70 binding and client transfer with progression of the Hsp90 reaction cycle.